General Check Up Cares for the Elderly - Ningsih, Dewi Andariya; Sakinah, Innama; Musyarrofah, Siti Hilmi; Fadlillah, Ufil Afifatul (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
The elderly activity with the theme of "General Check-Up Care for the Elderly" is one of the community's activities of community implementation as the implementation of Tri Dharma Perguruan Tinggi conducted by Midwifery Academy Ibrahimy Sukorejo Situbondo. This activity was carried out in Pokaan Village Village Hall of Kapongan on December 29, 2020. This activity was followed by elderly from 6 hamlets in Pokaan village. A proactive approach implemented in an integrated manner involving participants, health facilities and Ibrahimy midwifery Academy in order to maintain public health to achieve optimal quality of life. In the implementation of general Check-Up care elderly begins with elderly gymnastics activities, measurements of height, weight, blood pressure examination, uric acid examination and free treatment from Kapongan Community Health Center.